Inflation in supergravity and the volume modulus - Bernardo, H. de O [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this master thesis we attempt to implement inflation in supergravity with the volume modulus of large extra dimensions acting as the inflaton. The Langragian of chiral matter coupled with supergravity is derived from first principles and we review the standard cosmology and the consequences of an inflationary universe. Then we proceed to the analysis of inflation in supergravity and explain what are extra dimensions. Lastly, we construct a model of new inflation and look for its compatibility with the observacional results obtained from the Planck datellite

Nesta dissertação de mestrado, nós implementamos inflação na supergravidade com o volume de dimensões extras grandes atuando como inflaton. Trabalhamos no contexto N=1, d=4 supergravidade e com inflação gerada por um único campo escalar que assume valores subplanckianos. A Langrangeana de matéria chiral acoplada com supergravidade é derivada desde os primeiros princípios e nós revisamos a cosmologia padrão e as consequências de um universo inflacionário. Então procedemos para a análise da inflação na supergravidade e explicamos o que são dimensões extras. Por fim, nós construímos um modelo de nova inflação e procuramos pela sua compatibilidade com os resultados observacionais obtidos pelo satélite Planck
Keywords: Supergravidade; Cosmologia; Universo inflacionario; Supergravity